The Approximation of Laplace-Stieltjes Transforms Concerning Sun’s Type Function - Xia Shen; Hong Yan Xu (Journal of Function Spaces)
The main aim of this paper is to establish some theorems concerning the error EnF,β, the Sun’s type function Ur, and Muσ,F of entire functions defined by Laplace-Stieltjes transforms with infinite order converge in the whole complex plane. Our results exhibit the growth of Laplace-Stieltjes transforms from the point of view of approximation.